Genetic variants in PPARGC1B and CNTN4 are associated with thromboxane A2 formation and with cardiovascular event free survival in the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT). (February 2018) - McCarthy, Nina S.; Vangjeli, Ciara; Surendran, Praveen; Treumann, Achim; Rooney, Cathy; Ho, Emily; Sever, Peter; Thom, Simon; Hughes, Alun D.; Munroe, Patricia B.; Howard, Philip; Johnson, Toby; et al.
Abstract: Background and aims: Elevated urinary 11-dehydro thromboxane B2 (TxB2 ), a measure of thromboxane A2 formation in vivo, predicts future atherothrombotic events. To further understand this relationship, the genetic determinants of 11-dehydro TxB2 and their associations with cardiovascular morbidity were investigated in this study. Methods: Genome-wide and targeted genetic association studies of urinary 11-dehydro TxB2 were conducted in 806 Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) participants. Results: The strongest associations were in PPARGC1B (rs4235745, rs32582, rs10515638) and CNTN4 (rs10510230, rs4684343), these 5 single nucleotide polymorphisms (SNPs) were independently associated with 11-dehydro TxB2 formation. Haplotypes of 11-dehydro TxB2 increasing alleles for both PPARGC1B and CNTN4 were significantly associated with 11-dehydro TxB2, explaining 5.2% and 4.5% of the variation in the whole cohort, and 8.8% and 7.9% in participants not taking aspirin, respectively. In a second ASCOT population (n = 6199), addition of these 5 SNPs significantly improved the covariate-only Cox proportional hazards model for cardiovascular events (chisq = 14.7, p =0.01). Two of the risk alleles associated with increased urinary 11-dehydro TxB2 were individually associated with greater incidences of cardiovascular events - rs10515638 (HR = 1.31, p =0.01) and rs10510230 (HR = 1.25, p =0.007); effect sizes were larger in those not taking aspirin. Conclusions: PPARGC1B and CNTN4 genotypes are associated with elevated thromboxane A2 formation and with an excess of cardiovascular events. Aspirin appears to blunt these associations. If specific protection of PPARGC1B and CNTN4 variant carriers by aspirin is confirmed by additional studies, PPARGC1B and CNTN4 genotyping could potentially assist in clinical decision making regarding the use of aspirin in primary prevention. Highlights: This paper describes the first genome wide association study of thromboxane A2 formation. 5 SNPs in two genes, PPARGC1B and CNTN4, are associated with elevated thromboxane A2 formation in 806 ASCOT participants. The same SNPs are associated with an excess of cardiovascular events in an independent ASCOT population (n = 6, 199). These results suggest specific protection of aspirin for people with certain PPARGC1B and CNTN4 genotypesoman. If confirmed, PPARGC1B and CNTN4 genotyping could potentially provide guidance in the use of aspirin in primary prevention.